CONTRACTION MAPPING THEOREM OF THE SPACE OF FUZZY NUMBERS - Al-Zieady, Mary Gadbaan Thoubaan (Al-Nahrain Journal of Science, 2010)
In this paper we present fuzzy number and some of its properties it .Also, we define a newfuzzy metric D( a, b) of fuzzy numbers and discuss some of its algebraic operation of it . We provesome results to study the contraction mapping theorem of fuzzy numbers using modified approachdepending on the definition of function distance between fuzzy numbers.